2000
DOI: 10.1016/s0014-5793(00)01700-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel secretory leukocyte protease inhibitor‐binding protein involved in membrane phospholipid movement

Abstract: Previous studies have suggested that human salivary secretory leukocyte protease inhibitor (SLPI) inhibits HIV-1 by binding to a host cell surface protein of unknown identity. Using the yeast two-hybrid assay, we identified a gene sequence encoding a novel SLPI-binding protein (SLPI-BP). The 1.5-kb cDNA encodes a 318-amino acid protein with a predicted transmembrane segment near the C-terminus. Sequence analysis revealed that SLPI-BP is the human scramblase protein that is involved in the movement of membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…Our finding that the addition of SLPI to culture medium results in the up-regulation of cyclin D1 gene expression is perhaps indicative of an integral membrane-localized SLPI receptor/binding protein. This may or may not be functionally related to a recently described SLPI-interacting protein identified by yeast two-hybrid screen as scramblase, an integral membrane protein of 35-37 kDa involved in movement of membrane phospholipids (67)(68)(69). However, in another report (70), SLPI bound to a monocyte membrane protein of 55 kDa.…”
Section: Fig 8 Effects Of Tgf-␤1 On Ishikawa Cell Gene Expressionmentioning
confidence: 82%
“…Our finding that the addition of SLPI to culture medium results in the up-regulation of cyclin D1 gene expression is perhaps indicative of an integral membrane-localized SLPI receptor/binding protein. This may or may not be functionally related to a recently described SLPI-interacting protein identified by yeast two-hybrid screen as scramblase, an integral membrane protein of 35-37 kDa involved in movement of membrane phospholipids (67)(68)(69). However, in another report (70), SLPI bound to a monocyte membrane protein of 55 kDa.…”
Section: Fig 8 Effects Of Tgf-␤1 On Ishikawa Cell Gene Expressionmentioning
confidence: 82%
“…The integrin ␤ 3 expression plasmid was a kind gift of Dr. Erkki Ruoslahti (Burnham Institute). pTOPO-U6, Dab2-2112, pCI-neo-hDAB2, pCI-neo-His 9, pGST-⌬B, p82, ⌬B, ⌬N, and p82-S24A (S24A) have been described previously (2,7,14,34).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, another heparinbinding serine protease inhibitor, the secretory leukocyte protease inhibitor (SLP), is able to inhibit HIV-1. It has been suggested that SLP is an entry inhibitor but blocks a receptor distinct from chemokine receptors and CD4 (37)(38)(39)(40)(41)(42). Furthermore, another serine protease inhibitor, ␣ 1 -antitrypsin, also has been described as an inhibitor of HIV-1.…”
Section: Cd8 ϩ T-cells Of Seropositive Individuals Modify Serum Atiiimentioning
confidence: 99%